Pengaruh Strategi Branding Terhadap Minat Beli dengan Preferensi Merek Sebagai Moderasi - Adang Sutisna; Ajeng Andriani Hapsari; Rudy Haryanto; Muhammad Aqshel Revinzky; Eva Yuniarti Utami (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The business and trade world continues to experience growth and development. One of the industrial sectors that continues to experience development, especially in Indonesia, is the fashion industry, which is an industry that is growing and continuing to increase. In order to maintain the sustainability of its business, companies are faced with the creation of a strategy that is able to face competitive competition. This study aims to determine the effect of branding strategy on purchasing interest with brand preference as a moderation. The sampling technique in quantitative research is carried out randomly, data collection using research instruments, statistical data analysis with the aim of testing the established hypothesis. The results of this study found that branding strategy has an effect on purchasing interest. And brand preference as a moderating variable is able to moderate branding strategy on purchasing interest